Cabazitaxel-Loaded Nanocarriers for Cancer Therapy with Reduced Side Effects - Nagavendra Kommineni; Shaheen Mahira; Abraham J. Domb; Wahid Khan (MDPI AG, 2019)
Jevtana® is a micellar cabazitaxel (CBZ) solution that was approved for prostate cancer in 2010, and recently, this drug has been reported for breast cancer. The purpose of this study is to evaluate the mediated delivery of CBZ via liposomes and nanoparticles (NPs) for the treatment of breast cancer and compare these with a micellar formulation that is currently in clinical use. CBZ-loaded nanocarriers were prepared with particle sizes between 70–110 nm, and with the sustained in vitro release of CBZ for more than 28 days. Cytotoxicity studies on MCF-7 and MDA-MB-231 cells demonstrated the toxic potential of these nanocarriers. Cellular internalization revealed that NPs and liposomes have better permeability than micelles. Cell cycle analysis and apoptosis studies on MCF-7 and MDA-MB-231 cells confirmed G2/M phase arrest as well as cell death due to apoptosis and necrosis, where formulations were found to be effective compared to a micellar CBZ solution. Results from pharmacokinetic studies revealed that there is an increased circulation half-life and mean residence time for CBZ liposomes and NPs in comparison with a micellar CBZ solution. CBZ liposomes and NPs showed a reduction in hemolysis and neutropenia in comparison with a micellar CBZ solution in rats.